Preferences for psychological therapy in psychosis: trial participation, mode of treatment, and willingness to be randomised. (April 2014) - Sumner, Katherine; Haddock, Gillian; Hartley, Samantha; Kilbride, Martina; McCusker, Monica; Pitt, Liz; Woodward, Sarah; Barrowclough, Christine
Abstract Background: Psychological therapies for psychosis are well evidenced; however, service user preferences for psychological treatment and trial participation have been little researched. Aims: To investigate preferences for psychological treatments for psychosis and trial participation decisions within a sample of people with experience of psychosis. Method: Hypothetical preferences were assessed in 90 individuals diagnosed with non-affective psychosis: (a) willingness/unwillingness to participate in a psychological therapy trial; (b) willingness/unwillingness to be randomised to treatment condition; (c) preference for mode of therapy; (d) reasons for preferences; (e) socio-demographic and clinical characteristics associated with preferences. Results: Most participants reported willingness to participate in a therapy trial and preferred not to be randomly allocated. Reasons for preferences were diverse, and preferences were not associated with socio-demographic or clinical variables. Conclusions: The need for treatment choice in services for psychosis and further research in this area has been highlighted.